Avaliação bioquímica nutricional de cultivares de arroz - Matos, Amanda Dupas de (Universidade do Vale do Rio dos Sinos, 2014)
Rice is a cereal recognized by its functional properties mainly due to the bioactive compounds present in the outer layers of the grain. Although there is great phenotypic variety of rice, most part of has light brown pericarp and canbe consumed in the whole or polished form. Researchershave reported that rice canprovide nutritional and functional differences related to pigmentation of the pericarp.Therefore, the aim of this study was to analyze the amount of total soluble phenolic compounds (TSPC), antioxidant activity (AOA) and protein content of different rice cultivars with pigmented and non-pigmented pericarp and evaluate TSPC and AOA raw rice infusions. The AOA was determined from the concentration of TSPC and expressed in different units. The results showed differences in the quantity of TSPC and AOA (g/g DPPH) between the analyzed rice cultivars (raw and cooked intragroup) with emphasis on the black and red rice. After cooking, red and light brown rice differed in levels of TSPC and light brown rice in the AOA (g/g DPPH). Regarding the capacity to radical sequester (%Inhibition), there was no difference between the red and light brown rice, cooked and raw, and between cooked light brown and polished rice. In infusions, red rice was the one with most released TSPC to soaking water. As to %Inhibition of infusions, there were differences in the black and red rice compared to the light brown and polished rice. In protein characterization, there was no difference between cultivars (dry and wet basis intragroup), owever black, red and light brown grains differed when compared between groups (dry vs wet basis). The black rice showed stability of bioactive compounds such as less susceptibility to thermal degradation. The knowledge of the chemical and functional potential of the rice will allow the development of new possibilities using these grains as means for antioxidants aimed to health promotion.
Keywords: Oryza sativa; Compostos fenólicos; Atividade antioxidante; Phenolic compounds; Antioxidant activity; ACCNPQ::Ciências da Saúde::Nutrição